MASA DEPAN KEAMANAN ENERGI INDONESIA TELAAH KRITIS ATAS PROBLEMATIKA DAN PROSPEK PENGEMBANGAN KELAPA SAWIT SEBAGAI ENERGI ALTERNATIF DI INDONESIA - Akbar, Nuruddin Al (Jurnal Kawistara, 2013)
This article aims to understand the problems of the development of biodiesel made from Palm Oil.Understanding the problems become critical because of the successful development of Biodiesel is oneof the keys to overcome the problem of energy security of Indonesia. Until now, Indonesia experiencedenergy dependence, especially those in petroleum. Option is taken up today rely on oil imports.Whereas the import option raises problems of its own, including further burden the stateâs economy,due to government subsidies in order to reduce the sales price of oil at the community level. Thisarticle specifically examines the factors that led to the development of Biodiesel made from Palm Oil inIndonesia is not yet optimal. The article also highlights a number of the problems that are not directlyrelated to the development of Biodiesel, but can be a threat to national security in general. In addition,this article seeks to offer an alternative reform by using Collaborative Governance framework.